Atypical Intratemporal Meningioma Masquerading as Otitis Media—Clinical and Radiological Diagnostic Dilemma - Matish, Mrinal; Rathi, Abhishek; Moon, Manasi (Indian Journal of Radiology and Imaging, 2021)
Meningiomas are the most common intracranial extra-axial neoplasms with mostly straightforward radiological diagnosis; however, they can have unusual clinical and imaging manifestations posing diagnostic dilemma for radiologists and clinicians. The objective of this case report is to highlight the infrequent and misleading presentations of meningiomas to make an accurate diagnosis. A 65-year-old male patient presented with complaints of left recurrent otitis media and facial nerve palsy for past 6 months. On imaging, an aggressive predominantly cystic intracranial neoplasm was found in the left temporal fossa extending into the middle and external ear. Histopathological examination of the excised tumor revealed WHO grade I meningothelial meningioma. Meningiomas can show atypical imaging features such as large meningeal cysts, heterogenous or ring enhancement and aggressive features such as bone erosion. They can invade the middle ear and should be thought of while dealing with nonresponsive cases of otitis media.
Keywords: facial nerve; high-resolution computed tomography; magnetic resonance imaging; meningioma; otitis media